Testing the recent Santorini seismic activity for possible tidal triggering effect - Contadakis, Michael E.; Arabelos, Demeter N.; Vergos, G. (Bulletin of the Geological Society of Greece, 2017)
Based on the results of our studies for the tidal triggering effect on the seismicity of the Hellenic area, we consider the confidence level of earthquake occurrence - tidal period accordance as an index of tectonic stress criticality for earthquake occurrence and we check if the recent increase in the seismic activity at the Santorini island complex indicate that the faults Kameni and Columbo (to which the seismicity is clustered), (Chouliaras et al., 2013) are mature for a stronger earthquake. In this paper, we present the results of this test.